Factors Associated with the Utilization of Traditional Health Services among People with Non-Communicable Diseases in Indonesia: Findings from a Nationwide Survey - Iwan Abdi Suandana; Putu Ayu Swandewi Astuti; Pande Putu Januraga (Traditional and Integrative Medicine)
Globally, there is an increasing trend of morbidity and mortality from non-communicable diseases (NCDs). Traditional health service is one of the new approaches to support NCDs program. This study aimed to determine the prevalence and factors associated with the use of traditional health services among people with NCDs in Indonesia. We conducted a secondary analysis of integrated nationwide health and socio-economic survey data in 2018. Of the 127,198 people with NCDs included in the analysis, 38.7% of people with NCDs have ever used traditional health services, with the most common type being those that involve manual therapies. Compared to the reference group, likelihood of higher utilization of the traditional health service was among those aged 45-54 years (adjusted odds ratio (AOR) 1.19; p <0.001), from highest socioeconomic (AOR = 1.13, p <0.001), employed (AOR> 1, p <0.05), married/divorced (AOR> 1, p <0.001), has two type of NCDs (AOR 1.06, p 0.023), knows the existence of the nearest doctor/clinic (AOR 1.36, p <0.001) and hospital (AOR = 1.13, p 0.002) and has very easy access to health facility (AOR 1.34, p <0.001). Better socialization of traditional health services especially to the groups who have low utilization is important. The information should include the availability of traditional health services types, benefits, and advantages of using these services. It is also necessary to improve the quality and standardization of traditional health services to enhance public trust and increase the utilization of the services. Since a certain proportion of people with NCDs rely on traditional health services, improvement of the traditional health services quality is crucial, as well as engagement of these services to NCDs programs.